Retraction notice to “Reviewing the effect of CO2 and the sun on global climate” [Renew. Sustain. Energy Rev., 26(2013) 639–651] - Florides, Georgios A.; Christodoulides, Paul; Messaritis, Vassilios (My University, 2018)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (http://www.elsevier.com/locate/withdrawalpolicy). This article has been retracted at the request of the Editor-in-Chief due to duplicate publication based on parts of the authors’ own book chapter ‘Global Warming: CO2 vs Sun,’ by Georgios Florides, Paul Christodoulides and Vassilios Messaritis, published: September 27th 2010, DOI: 10.5772/10283. One of the conditions of submission of a paper for publication is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.
Keywords: Retraction notice; Sun; Global climate